Motoric Development of Class V-1 at MIN 20 Aceh Besar Through Traditional Sports Games - Riyanto, Riyanto (Universitas Syiah Kuala, 2024)
This research aims to observe the physical motoric development of elementary age children achieved by providing learning methods using traditional sports equipment and games.. Teachers and parents have an important role in honing and monitoring children's physical-motor development so that they can grow and develop well. Motoric development is divided into two, namely gross motor skills and fine motor skills. Motoric development and physical development cannot be separated, because physical development can provide stimulation for motoric development which is related to movement skills. This research uses descriptive qualitative methods to obtain data by observation and documentation. This research was conducted at Madrasah Ibtidaiyyah Negeri 20 Aceh Besar. The sample for this research was all students in class V-1 with a theoretical study of students' physical-motor development. The results of the study show that the physical-motor development of all class V-1 students is developing well because teachers use a variety of learning methods to develop students' physical-motor development well.